Impacts of the Tagang programme on an indigenous Dayak community. Issue 3 (3rd July 2021) - Keling, William; Ho, Poh Ling; Yap, Ching Seng; Entebang, Harry
ABSTRACT: The study assesses the impacts of the  Tagang  programme – a practice of preserving riverine fish species in the restricted area, for nature conservation and ecotourism development – on an indigenous community in Malaysia, using the empowerment framework. The data are collected from in-depth interviews with 27 key informants. Using thematic analysis, this study reveals three main themes – nature conservation, ecotourism development, and participation of local community. Through the  Tagang  programme, the river ecological system has improved. The village has enhanced community cohesion and collaboration, and developed new ecotourism activities for income generation. The indigenous  Dayak  community is empowered to lead and operate in the  Tagang  programme in their village which has resulted in positive economic, social, and environmental benefits.